Inflammatory cell distribution in guinea pig airways and its relationship to airway reactivity - Fiona Westerhof; Wim Timens; Annemiek van Oosten; Annet B. Zuidhof; Nathalie Nauta; Martin Schuiling; Johannes T. W. M. Vos; Johan Zaagsma; Herman Meurs; Wilko Coers (Hindawi Limited, 2001)
Although airway inflammation and airway hyperreactivity are observed after allergen inhalation both in allergic humans and animals, little is known about the mechanisms by which inflammatory cells can contribute to allergen-induced airway hyperreactivity. To understand how inflammatory cell infiltration can contribute to airway hyperreactivity, the location of these cells within the airways may be crucial.